2015
DOI: 10.1177/0363546515578838
|View full text |Cite
|
Sign up to set email alerts
|

Association of Meniscal Status, Lower Extremity Alignment, and Body Mass Index With Chondrosis at Revision Anterior Cruciate Ligament Reconstruction

Abstract: Background Knees undergoing revision ACL reconstruction (rACLR) have a high prevalence of articular cartilage lesions. Hypothesis The purpose of this study was to test the hypothesis that the prevalence of chondrosis at the time of rACLR is associated with meniscus status and lower extremity alignment. Study design Cross sectional study. Methods Data from the prospective Multicenter ACL Revision Study (MARS) cohort was reviewed to identify patients with pre-operative lower extremity alignment films. Lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 49 publications
(70 reference statements)
2
28
0
Order By: Relevance
“…[21][22][23] In a prospective study by Brophy et al, 246 patients were evaluated at the time of revision ACL reconstruction, and it was demonstrated that more varus alignment and elevated BMI were associated with worse chondral lesions in the medial compartment. 24 A few studies have demonstrated the effect of BMI on the occurrence of intra-articular injuries accompanying primary ACL tear. Kluczynski et al examined sex-specific predictors and demonstrated that BMI was one of the predictors of associated intraarticular injuries for males and females.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] In a prospective study by Brophy et al, 246 patients were evaluated at the time of revision ACL reconstruction, and it was demonstrated that more varus alignment and elevated BMI were associated with worse chondral lesions in the medial compartment. 24 A few studies have demonstrated the effect of BMI on the occurrence of intra-articular injuries accompanying primary ACL tear. Kluczynski et al examined sex-specific predictors and demonstrated that BMI was one of the predictors of associated intraarticular injuries for males and females.…”
Section: Discussionmentioning
confidence: 99%
“…6,13,24,27 This collaboration consists of a group of 83 sports medicine fellowship trained surgeons across 52 sites. Surgeons are a near equal mix of academic and private practitioners.…”
Section: Methodsmentioning
confidence: 99%
“…BMI has also been found to be associated with other intra-articular injuries observed during ACL reconstructions. 30,31…”
Section: Introductionmentioning
confidence: 99%